Lymphocyte response is enhanced by supplementation of elderly subjects with selenium-enriched yeast - Peretz, A; Nève, J; Desmedt, J; Duchateau, J; Dramaix, M; Famaey, JP (The American journal of clinical nutrition, 1991)
The effect of selenium supplementation on plasma selenium concentrations and lymphocyte-proliferation responses to mitogens was investigated in 22 elderly institutionalized subjects. Subjects were assigned to a 6-mo trial with either 100 µg Se/d (as selenium-enriched yeast) or a placebo. Plasma selenium concentrations of the selenium-supplemented group increased from 0.84 ± 0.26 to 1.55 ± 0.33 µmol/L (x̄ ± SD) after 2 mo and the values plateaued thereafter. The mean response of lymphocytes to mitogens in elderly subjects tended to be lower than responses in healthy adults, although responses remained within the 5–95% confidence-interval limit for healthy adults. During selenium supplementation the proliferative response to pokeweed mitogen increased significantly (+79% of baseline concentrations after 4 mo, P < 0.01) and reached the upper limit of the usual range for adults after 6 mo (+138%, P < 0.001). In accordance with previous studies in animals and in vitro, this investigation demonstrates for the first time immunostimulatory properties of selenium-enriched yeast in elderly humans.